2009
DOI: 10.1016/j.jesp.2009.08.005
|View full text |Cite
|
Sign up to set email alerts
|

An implicit measure of anti-gay attitudes: Prospective associations with emotion regulation strategies and psychological distress

Abstract: Members of stigmatized groups are at increased risk for mental health problems, and recent research has suggested that emotion dysregulation may be one mechanism explaining the stigma-distress association. However, little is known regarding characteristics that predict vulnerabilities to emotion dysregulation and subsequent distress. We examined whether anti-gay attitudes would predict poorer emotion regulation and greater psychological distress in 31 lesbian, gay, and bisexual (LGB) respondents. Respondents c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 38 publications
(47 reference statements)
14
92
1
Order By: Relevance
“…Until this process is more specifically modeled in future research, we are left to grapple with the possibility that this linkage is driven wholly or in part by some other third common factor (e.g., emotionality). However, consistent with the causal pattern we assume wherein attitudes drive reported rumination, Hatzenbuehler et al (2009) found that self-reported brooding rumination fully mediated the link between implicit anti-gay attitudes (as the initial predictor) and psychological distress among LGB respondents. Furthermore, to disentangle our confound, it will be informative to look at men's stereotyping of women (Do men, especially traditional men, expect women to ruminate more?)…”
Section: Discussionsupporting
confidence: 80%
“…Until this process is more specifically modeled in future research, we are left to grapple with the possibility that this linkage is driven wholly or in part by some other third common factor (e.g., emotionality). However, consistent with the causal pattern we assume wherein attitudes drive reported rumination, Hatzenbuehler et al (2009) found that self-reported brooding rumination fully mediated the link between implicit anti-gay attitudes (as the initial predictor) and psychological distress among LGB respondents. Furthermore, to disentangle our confound, it will be informative to look at men's stereotyping of women (Do men, especially traditional men, expect women to ruminate more?)…”
Section: Discussionsupporting
confidence: 80%
“…Higher scores reflected more brooding. The measure had good internal consistency (α = .85) in a sample of LGB individuals (Hatzenbuehler, Dovidio, Nolen-Hoeksema, & Phills, 2009). …”
Section: Response Styles Questionnaire (Treynor Gonzalez and Nolen-homentioning
confidence: 97%
“…According to the psychological mediation framework, stress comes first in the causal chain leading to physiological and psychological health outcomes (i.e., stress → psychological mediators → psychopathology). Furthermore, Hatzenbuehler et al (2009a, b) argue that distal stigma-related stressors affect psychopathology through cognitive, social/interpersonal, and emotional channels. In particular, he and his colleagues have shown through a series of experimental and longitudinal studies that stigma-related stress increases emotion dysregulation (e.g., increased rumination, engagement in impulsive behaviors), which in turn can lead to risk for depression, anxiety, and substance abuse problems among sexual minority individuals (e.g., Hatzenbuehler et al 2009a, b).…”
Section: A Review and Critique Of Racial Microaggressions Literaturementioning
confidence: 99%
“…Furthermore, Hatzenbuehler et al (2009a, b) argue that distal stigma-related stressors affect psychopathology through cognitive, social/interpersonal, and emotional channels. In particular, he and his colleagues have shown through a series of experimental and longitudinal studies that stigma-related stress increases emotion dysregulation (e.g., increased rumination, engagement in impulsive behaviors), which in turn can lead to risk for depression, anxiety, and substance abuse problems among sexual minority individuals (e.g., Hatzenbuehler et al 2009a, b). Applying this model to microaggressions, racial microaggression may be conceptualized as a stressor that mediates the effects of the racial minority status on physical and psychological health outcomes (see Fig.…”
Section: A Review and Critique Of Racial Microaggressions Literaturementioning
confidence: 99%